Growth pattern and phenological stages of peach (Prunus persica) under subtropics - SRIVASTAVA, K K; RAJAN, S; KUMAR, DINESH; SINGH, S R; VERMA, H C (The Indian Journal of Agricultural Sciences, 2020)
Peach exhibits different phenological stages throughout its vegetative period in response to environmental conditions. Fifteen different stages were identified during the annual growing cycle of low chill peach at subtropical condition. Dormancy break first started in Saharanpur Prabhat and Pant Peach-1 during last week of January. Initiation of bloom first (8–20 Feb) noticed in Flordaprince, Sharbati Surkha and Earligrande, while full bloom was first noticed in Flordaprince Pratap and Pant Peach-1 and end of flowering earliest in Pant Peach-1 (mid to end February). Fruit maturity is important character for good market price, early maturity was recorded in Sharbati, Sharbati Surkha, Flordaprince and Pratap (last week of April to May 1st week). Maximum production efficiency (4.98 fruit/cm2 TCSA,) was recorded in Pratap. Fruit weight varied from 34.85–80.57 g in different cultivars. Maximum heat use efficiency (HUE) 51.87 kg/cm2 TCSA degree days was registered in Pratap and Earligrande (31.82 kg/cm2 TCSA degree/day/ year). For successful cultivation of low chill peaches under subtropics Flordaprince, Sharbati and Sharbati Surkha selected as early maturing, Shan-e-Punjab, Earligrande and Pratap as mid maturing and Pant Peach-1 has been found as late maturing cultivars.